Extending the dosing interval of COVID-19 vaccination leads to higher rates of seroconversion in people living with HIV - Wang, Yi; Li, Jianhua; Zhang, Wenhui; Liu, Shourong; Miao, Liangbin; Li, Zhaoyi; Fu, Ai; Bao, Jianfeng; Huang, Lili; Zheng, Liping; Li, Er; Zhang, Yanjun; et al. (Frontiers in Immunology, 2023)
Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is an effective way of protecting individuals from severe coronavirus disease 2019 (COVID-19). However, immune responses to vaccination vary considerably. This study dynamically assessed the neutralizing antibody (NAb) responses to the third dose of the inactivated COVID-19 vaccine administered to people living with human immunodeficiency virus (HIV; PLWH) with different inoculation intervals. And risk factors associated with seroconversion failure after vaccination were identified via Cox regression analysis. A total of 171 participants were recruited: 63 PLWH were placed in cohort 1 (with 3-month interval between the second and third doses), while 95 PLWH were placed in cohort 2 (with 5-month interval between the second and third doses); 13 individuals were enrolled as healthy controls (HCs). At 6 months after the third vaccination, PLWH in cohort 2 had higher NAb levels (GMC: 64.59 vs 21.99, P < 0.0001) and seroconversion rate (68.42% vs 19.05%, P < 0.0001). A weaker neutralizing activity against the SARS-CoV-2 Delta variant was observed (GMT: 3.38 and 3.63, P < 0.01) relative to the wildtype strain (GMT: 13.68 and 14.83) in both cohorts. None of the participants (including HCs or PLWH) could mount a NAb response against Omicron BA.5.2. In the risk model, independent risk factors for NAb seroconversion failure were the vaccination interval (hazed ration [HR]: 0.316, P < 0.001) and lymphocyte counts (HR: 0.409, P < 0.001). Additionally, PLWH who exhibited NAb seroconversion after vaccination had fewer initial COVID-19 symptoms when infected with Omicron. This study demonstrated that the third vaccination elicited better NAb responses in PLWH, when a longer interval was used between vaccinations. Since post-vaccination seroconversion reduced the number of symptoms induced by Omicron, efforts to protect PLWH with risk factors for NAb seroconversion failure may be needed during future Omicron surges.